ON THE RESULTS OF THE SPECIAL PARLIAMENTARY ELECTIONS IN KAZAKHSTAN - SHAYMERGENOV, Timur (CENTRAL ASIA AND THE CAUCASUS, 2007)
The current political season will certainly occupy a special place in Kazakhstan’s most recent history. It is no exaggeration to say that the political reform going on in the country is a symbolic event that has significantly changed the political arena and configuration of forces in the republic. This process was launched in May when amendments to the country’s Constitution called upon to bring the economic and political development processes in Kazakhstan into harmony with each other were adopted. They were primarily aimed at introducing a presidential-parliamentary form of rule in the country. The president’s deliberate transfer of some powers to the political parties and the parliament was not only a sign of the constructive development of the political system, but also a strategically tested step that greatly accelerated political modernization in Kazakhstan. The change in the parliament’s status and possibilities led to disbandment of the lower house and the decision to hold special elections to the Majilis on 18 August, 2007.1 Analysts give a variety of reasons why the deputy corps of the third convocation became a thing of the past, but this step seems very logical, since it was dictated by the amendments to the Constitution, and they, in turn, were a demand of the times. There are no other clear reasons for the disbandment, since the Majilis’ activity was not criticized in the government or society, and the house operated quite efficiently. This step also meets the interests of Kazakhstan’s democratic development and the tasks of the country’s accelerated modernization. Elections according to the proportional system held for the first time in Kazakhstan’s history were not only an innovation for all the political forces and society as a whole but were also a test of the party system’s maturity. Few had any idea what a political party’s tactics, or its relations with the republic’s elite, should be in the new situation. For the first time, a list of leaders had to be compiled, which was offered to the voters as the party’s overall image. Public opinion polls acquired an entirely different nature, and the fervor aroused by the party ratings on a national scale was one of the most entertaining elements of the past election marathon.2 In so doing, many experts christened them “no-intrigue elections” even before the actual campaign began, since the favorite and the results were known in advance. The results surprised everyone and gave rise to all kinds of different assessments. But all the same, despite all the ambiguity and unexpectedness of the election results, political reform in Kazakhstan is an important and long-term step, for the country has in fact transferred from one system to another—from the ex-Soviet Kazakh S.S.R. and a post-Soviet new formation with unclear legitimacy to a systemic national state.3 The past election campaign was a logical continuation of this reform. The government gave society another clear signal that it was steering a steady course toward democratization of the country and that political modernization would not be halted or conserved